"I SLICED MY FLESH INTO PAPER, AND GROUND MY LIVER INTO INK": WANG CIHUI'S (1593-1642) SENSUALIST POETRY AS AN ALTERNATIVE ROUTE TO SELF-REALIZATION. (1st May 2013) - Xiaorong, Li
Abstract : Wang Yanhong ( zi Cihui, 1593-1642) was active in the last decades of the Ming. Because of his particular interest in representing erotic and amorous experiences with women in rich and sensual detail, his poetry was controversial and condemned by those who upheld a Confucian poetics in which poetry was meant to express the poet's moral intentions and social criticism. This paper is the first attempt to translate Wang's poems into English and to closely examine them in the contexts of Chinese poetic tradition and late Ming literati culture. I argue that his "decadent" aestheticization of his amorous and emotional experiences with women was related to his identity as a "loser" who failed in the civil service examinations but sought in writing poetry an alternative path of self-realization. His poetics served to fulfill his ambition to become a poet of extraordinary creativity and aestheticism, even as it reveals his sense of self as an "invalid" member of his society.